Advances in tuning the "d33 ∝ 1/Td" bottleneck: simultaneously realizing large d33 and high Td in Bi0.5Na0.5TiO3-based relaxor ferroelectrics. Issue 18 (29th April 2020) - Yin, Jie; Tao, Hong; Zhang, Yuxing; Han, Jihui; Huang, Yanli; Li, Zhitao; Zhang, Xingmin; Wu, Jiagang
Abstract : We report the simultaneous achievement of a large d 33 and a high depolarization temperature ( T d ) in Bi0.5 Na0.5 TiO3 -based complex oxides. Abstract : For Bi0.5 Na0.5 TiO3 -based complex oxides, a critical bottleneck is that a higher depolarization temperature T d is often obtained at the cost of sacrificing their piezoelectricity d 33 ( d 33 ∝ 1/ T d ), which severely restricts the further development of this kind of promising material. Here, by combining compositional materials selection with rapid quenching in liquid nitrogen from ultra-high temperatures, we report an advance in simultaneously achieving a large d 33 (232 ± 5 pC N −1 ) and a high T d (188 °C) in Bi0.5 Na0.5 TiO3 -based complex oxides. In situ characterization indicates that the superior performance (232 pC N −1 < d 33 < 281 pC N −1 ) can be maintained in a wide working temperature range (25 °C < T < 185 °C). A series of quenching treatments and multi-scale structural analyses (ion environment, lattice distortion and domain evolution) reveal that the increased coherence length (the size of unit cells sharing the same ferroelectric symmetry) of the ferroelectric lattice enhances the ferroelectric ordering and leads to the deferred T d . Theoretical simulations and experimental results validate the quenching-induced redistribution of A-site ions. And the resulting enhanced ferroelectric polarization compensates the degenerated dielectric response, accounting for the effectively increased T d without decreasing the superior piezoelectric response. This research provides a paradigm for designing high-performance Bi0.5 Na0.5 TiO3 -based electromechanical materials in a wide working temperature range.